Selling health and happiness how influencers communicate on Instagram about dieting and exercise: mixed methods research - Pilgrim, Katharina (BMC Public Health, 2019)
BACKGROUND: Eating disorders among adolescents are an ongoing public health concern. Sustainable health promotion programmes require a thorough understanding of the social context in which minors engage. Initial studies show that young people make extensive use of social networks in order to exchange experiences and gather information. During this process their (buying) behaviour is significantly affected by so-called influencers. METHODS: The exploratory research studies non-campaign driven health communication on dieting and exercise by influencers in social networks with a focus on content, techniques and visible impact. In a mixed methods approach, we initially analysed 1000 posts from influencers on Instagram quantitatively. Subsequently we conducted an in-depth content analysis of 9 extreme and 27 typical communication threads. RESULTS: Influencers gain the trust and friendship of their followers by designing body-shape focused visual content and targeted communication techniques. They identify and define diet and exercise as factors to be controlled for body perfection. By consuming dietary supplements and wearing tight-fitting branded sportswear, influencers promise a simplified way of optimizing one’s appearance as the key to happiness. Direct and surreptitious advertising of industry-specific products constitutes the communicative focus. At the same time, minors identify with the roles and ideals demonstrated by influencers and their needs are satisfied on several different levels. This creates a relationship of dependency between influencers and their followers. CONCLUSIONS: The dynamics in the field of health communication by influencers on social networks will become increasingly important in the coming years. This is largely due to the targeted demand on the part of (mainly) underage users and the high attractiveness of influencer marketing on the part of companies. Influencers suggest a dependence on happiness, well-being, health and beauty. Only those who create a body shaped through control and discipline are healthy and beautiful - and can be happy. The indirectly communicated conclusions, which can be considered as extremely critical, illustrate the need for action in order to protect and positively accompany young people in their psychological and physical development. The shift of authority figures within Generation Z, as well as identified communication techniques, can be considered and may be harnessed by targeted, group-oriented campaign designs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-019-7387-8) contains supplementary material, which is available to authorized users.